1997
DOI: 10.1177/001440299706300406
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Research-to-Practice Gap

Abstract: The contribution of research findings to the education of Americas students, including those with disabilities, depends on the quality of and market demand for research findings. This paper presents a rationale and suggestions for increasing the quality of and market demand for research findings as a vital component of any serious effort to improve American education. Responses to the paper are from representatives of the American Federation of Teachers; Learning Disabilities Association; National Alliance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
228
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(232 citation statements)
references
References 3 publications
2
228
0
2
Order By: Relevance
“…Recently, special educators have called for a new agenda of prevention within special education (Farmer, Quinn, Hussey, & Holahan, 2001;Forness et al, 2000;Kamps, Kravits, Stolze, & Swaggart, 1999;Kauffman, 1999a;Walker et al, 1998). Others have called on school psychologists and special educators to make better use of evidence-supported prevention/intervention (Carnine, 1997;Simpson, 1999;. In particular, some leaders in the field have suggested that special educators should embrace primary and secondary prevention, which, when effectively implemented, can reduce the need for tertiary prevention and other forms of costly treatments for special education students (see Farmer et al, 2001;Forness et al, 2000;Kauffman, 1999b).…”
mentioning
confidence: 99%
“…Recently, special educators have called for a new agenda of prevention within special education (Farmer, Quinn, Hussey, & Holahan, 2001;Forness et al, 2000;Kamps, Kravits, Stolze, & Swaggart, 1999;Kauffman, 1999a;Walker et al, 1998). Others have called on school psychologists and special educators to make better use of evidence-supported prevention/intervention (Carnine, 1997;Simpson, 1999;. In particular, some leaders in the field have suggested that special educators should embrace primary and secondary prevention, which, when effectively implemented, can reduce the need for tertiary prevention and other forms of costly treatments for special education students (see Farmer et al, 2001;Forness et al, 2000;Kauffman, 1999b).…”
mentioning
confidence: 99%
“…Trustworthiness refers to the extent to which the research methods and data underlying findings can be considered reliable and valid representations of reality (Carnine, 1997;. Trustworthiness (i.e., validity) of research findings is based on many considerations, including rigor of research design and quality of study method.…”
Section: Trustworthy Research Is Open Transparent and Reproduciblementioning
confidence: 99%
“…For years, educational practice has been plagued by the infamous research-practice gap (e.g., Carnine, 1997;Elmore, 1996;Gersten, Vaughn, Deshler, & Schiller, 1997;Greenwood & Abbott, 2001;Kauffman, 1996;Kennedy, 1997;Robinson, 1998). Too often, research in special education has been limited to small-scale fragmented research initiatives.…”
Section: Orie Of the Major Findings Of The Bright Futures Formentioning
confidence: 99%